2014
DOI: 10.1177/1934578x1400900411
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Cultures of Bituminaria bituminosa: Pterocarpan, Furanocoumarin and Isoflavone Production and Cytotoxic Activity Evaluation

Abstract: Bituminaria bituminosa L. is known for producing several compounds with considerable pharmaceutical interest, such as phenylpropanoids, furanocoumarins and pterocarpans. In vitro cultures of seedlings, shoots, and callus have been produced to obtain plant materials useful for the production of these metabolites. The secondary metabolite profile was evaluated by HPLC-DAD. The extracts of all the in vitro material contained the flavonoid daidzein, while plicatin B, erybraedin C and bitucarpin A were found only i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 28 publications
2
18
1
Order By: Relevance
“…During the vegetative stage, mycorrhizal plants contained significantly higher amounts of angelicin and psoralen compared with control plants, where these molecules were not detectable; such compounds represent the typical furanocoumarins in Fabaceae, in particular angelicin, which has been reported as the major component of furanocumarins in wild‐grown B. bituminosa leaves sampled in Elba Island (D'Angiolillo et al . ). During the flowering stage, AMF inoculation decreased the production of bitucarpin A and erybraidin C, the latter representing the major component of pterocarpans in wild‐grown B. bituminosa leaves (D'Angiolillo et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…During the vegetative stage, mycorrhizal plants contained significantly higher amounts of angelicin and psoralen compared with control plants, where these molecules were not detectable; such compounds represent the typical furanocoumarins in Fabaceae, in particular angelicin, which has been reported as the major component of furanocumarins in wild‐grown B. bituminosa leaves sampled in Elba Island (D'Angiolillo et al . ). During the flowering stage, AMF inoculation decreased the production of bitucarpin A and erybraidin C, the latter representing the major component of pterocarpans in wild‐grown B. bituminosa leaves (D'Angiolillo et al .…”
Section: Discussionmentioning
confidence: 97%
“…During the flowering stage, AMF inoculation decreased the production of bitucarpin A and erybraidin C, the latter representing the major component of pterocarpans in wild‐grown B. bituminosa leaves (D'Angiolillo et al . ). The only data available on the role of AMF in the development and growth of B. bituminosa concern its ability to survive in polluted sites, which increased when inoculated with AMF (Alguacil et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the antitumor effects of angelicin in human cervical carcinoma, as well as the mechanisms underlying its actions, are largely unknown. D'Anqiolillo et al (24) reported that angelicin exerts cytotoxic activity on HeLa cells, but did not elucidate the exact mechanism by which this occurs (24). Therefore, the aim of the present study was to assess the effects of angelicin on the human cervical carcinoma cell lines, HeLa and SiHa, and to investigate the molecular mechanisms underlying its action.…”
Section: Discussionmentioning
confidence: 99%
“…Further our observation of green spots on callus indicate the high callus growth rate as well callus ability to produce shoots. Researchers have succeeded in producing several valuable secondary phytochemicals in unorganized callus cultures [ 14 , 35 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%